2006
DOI: 10.1073/pnas.0609635104
|View full text |Cite
|
Sign up to set email alerts
|

Identification of alterations in DNA copy number in host stromal cells during tumor progression

Abstract: The interactions between cancer cells and the surrounding host stromal tissue play a critical role in tumor progression and metastasis, but the molecular nature of this relationship remains largely uncharacterized. Furthermore, although genetic changes of neoplastic cells in tumors contribute significantly to tumor progression, it is not known whether similar changes occur in the adjacent host stromal microenvironment and whether they contribute to or inhibit tumorigenesis. To address this question in an unbia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 46 publications
1
39
0
1
Order By: Relevance
“…Our results could be in agreement with a number of studies suggesting that stromal cells have to co-evolve with the tumoural cells per se to facilitate tumour growth (Kurose et al, 2002;Allinen et al, 2004;Pelham et al, 2006;Bian et al, 2007;Patocs et al, 2007). In the case of haematological cells, it is well documented that lympho-stromal interactions are essential in thymic development and function (Anderson and Jenkinson, 2001) and that bone marrow stromal cells may contribute to prevent apoptosis of non-Hodgkin's lymphoma cells (Lwin et al, 2007).…”
Section: Discussionsupporting
confidence: 81%
“…Our results could be in agreement with a number of studies suggesting that stromal cells have to co-evolve with the tumoural cells per se to facilitate tumour growth (Kurose et al, 2002;Allinen et al, 2004;Pelham et al, 2006;Bian et al, 2007;Patocs et al, 2007). In the case of haematological cells, it is well documented that lympho-stromal interactions are essential in thymic development and function (Anderson and Jenkinson, 2001) and that bone marrow stromal cells may contribute to prevent apoptosis of non-Hodgkin's lymphoma cells (Lwin et al, 2007).…”
Section: Discussionsupporting
confidence: 81%
“…Confirming Tavassoli's observations using a xenograph model, David Botstein and his team used a nonmicrosatellite-based genomewide approach to analyze for somatic copy number variation in the mouse stromal cells in the microenvironment of xenografted human carcinoma-epithelial cells (4). These investigators found numerous amplifications and deletions of genomic regions in the host (murine) stroma surrounding the xenografted human carcinoma cells.…”
Section: Somatic Genomic Alterations In Tumor Stroma Of Different Typmentioning
confidence: 90%
“…TAMs can produce high amounts of reactive compounds, including reactive oxygen and nitrogen species that can interact with DNA, inducing mutations in surrounding epithelium (Maeda and Akaike 1998;Lin et al 2001). This property may explain mutations seen in local tumor endothelium and stromal cells (Pelham et al 2006). Alternatively, TAMs can produce cytokines that are capable of inducing genetic abnormalities.…”
Section: Infiltrating Inflammatory Cellsmentioning
confidence: 99%
“…It has been recently suggested that stromal fibroblasts and endothelial cells may acquire genetic alterations similar to those seen in tumor cells and this coevolution may provide growth and migratory advantages to both cell types (Pelham et al 2006). In vivo, migrant cell clusters retain cell-cell junctions, protrude into adjacent tissue driven by leading "pathfinder" cells, and can be detected in lymphatic vessels (Carr 1983) and in peripheral blood (Liotta et al 1976;Brandt et al 1996;Friedl and Brocker 2000).…”
Section: Migratory Neighbors and Distant Invaders Genes And Developmentmentioning
confidence: 99%